2020
DOI: 10.24843/coping.2020.v08.i04.p03
|View full text |Cite
|
Sign up to set email alerts
|

Hambatan dan Strategi komunikasi efektif dalam perawatan kanker

Abstract: Komunikasi terapeutik diakui sebagai kunci untuk perawatan kanker yang berkualitas, tetapi komunikasi perawat-pasien dalam perawatan kanker adalah hal menantang dan kompleks, selain data yang mengeksplorasi komunikasi perawat-pasien masing sangat kurang. Tujuan penelitian ini adalah untuk melaporkan hasil temuan tentang perspektif perawat, pasien dan keluarga terkait hambatan dan strategi komunikasi dalam perawatan kanker. Penelitian ini merupakan penelitian fenomenologi yang dilakukan di RS. PKU Muhammadiyah … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
1
0
1
Order By: Relevance
“…This is in line with previous research, which states that in providing information to patients, nurses need to prepare themselves beforehand both in their mental and knowledge. 10 This study also identified the limited time nurses spend with patients and the high workload that causes the scarcity of time with patients to become a barrier to therapeutic communication. Similar findings also appeared in other studies, which stated that the lack of time to sit with patients made nurses unable to show empathy.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with previous research, which states that in providing information to patients, nurses need to prepare themselves beforehand both in their mental and knowledge. 10 This study also identified the limited time nurses spend with patients and the high workload that causes the scarcity of time with patients to become a barrier to therapeutic communication. Similar findings also appeared in other studies, which stated that the lack of time to sit with patients made nurses unable to show empathy.…”
Section: Discussionmentioning
confidence: 99%
“…Hasil yang sama ditemukan pada penelitian Issa et al, (2021) menunjukkan bahwa sumber informasi utama untuk skrining/deteksi awal kanker serviks adalah dokter spesialis ginekologi (75,0%) dan dokter umum (40,1%). Hal ini menunjukkan pentingnya petugas kesehatan dalam memberikan informasi kepada masyarakat tentang kanker serviks dan skriningnya, di mana kurangnya rekomendasi dari para profesional kesehatan adalah hambatan paling umum dalam skrining untuk kanker serviks (Minanton & Rochmawati, 2020;Rochmawati & Minanton, 2021). Perempuan yang diberi informasi tentang pemeriksaan gratis memiliki kemungkinan 4,27 kali lebih besar untuk hadir skrining untuk kanker serviks http://jurnalilmiah.ici.ac.id/index.php/JI Vol.7 No.2 Januari 2024 (110) dibandingkan dengan mereka yang tidak mendapatkan informasi (Nwabichie et al, 2018;Salehiniya et al, 2021).…”
Section: Hubungan Peran Tenaga Kesehatan Dengan Perilaku Deteksi Dini...unclassified
“…Patients and their families need detailed information about the disease and its treatment. The ability to communicate in a respectful and therapeutic manner in a comfortable environment is crucial to providing care that improves quality of life [4], [11], [19], [20].…”
Section: Experience Of Comfortmentioning
confidence: 99%